Pater Filucius - Busch, Wilhelm, 1832-1908 (Salt Lake City, UT : Project Gutenberg, 2004)
"Pater Filucius" by Wilhelm Busch is an anticlerical satirical picture story published in 1872. Set against Germany's Kulturkampf, the tale follows wealthy Gottlieb Michael as the cunning Jesuit Pater Filucius schemes to steal his fortune. Through romantic pursuits of Michael's cousin and Catholic aunt, the priest enlists socialist accomplices in a sinister plot. Three loyal friends$1 (Ba constable, teacher, and farmer$1 (Bmust intervene to save Michael. Busch's controversial satire became his most influential work, reaching massive sales despite later being called his weakest anticlerical effort. (This is an automatically generated summary.)s
Wikipedia page about this book: https://de.wikipedia.org/wiki/Pater_Filucius
Release date is 2004-12-13
E-text prepared by Inka Weide and the Project Gutenberg Online Distributed Proofreading Team
Keywords: German poetry -- 19th century